Assessing Measurement Invariance of Customer Value Scale across Two Distinct Groups of Managers and Customers - Nasution, Hanny N. (The South East Asian Journal of Management, 2008)
The paper investigates measurement invariance of customer value construct across different populations (managers and customers). The purpose in doing this analysis is that whether the constructs were being mapped from two disctinct groups. Data for this study comes from two samples: hotel managers and hotel guests. All classified hotels across Indonesia were included. A total 231 managers and 385 customers responded to the survey. The results indicate the cocnceptualisation and operationalisation of customer value developed in this study, does not significantly generalise across managers and customers. The results further indicate that the construct has robust psychometric properties; however, the construct was perceived differently by managers and customers.